Langerhans-Cell Histiocytoses - Epidemiology, Classification, Clinical Features, Diagnosis, Complications, Treatment and Prognosis - Vera Papochieva; Dimitrinka Miteva; Penka Perenovska; Guergana Petrova (Journal of Biomedical & Clinical Research)
Histiocytoses comprise a group of diverse diseases of unknown etiology with various clinical presentation and evolution. The underlying pathology is characterised by accumulation and infiltration of variable numbers of cells of the monocyte-macrophage line in the affected tissues and organs. Histiocytoses are divided into three major classes: Langerhans cell histiocytosis (LCH), non- Langerhans cell histiocytosis, and malignant histiocytic disorders. The term LCH (also known in the past as histiocytosis X) encompasses the following rare diseases: Eosinophilic Granuloma, Hand-Schuller-Christian disease, Letterer-Siwe disease, Hashimoto-Pritzker disease, in which accumulation of pathologic Langerhans cells (LCs) leads to tissue damage. LCs usually reside in the skin and ensure protection against infections by destroying foreign substances. LC accumulation is caused by antigen stimulation and inadequate immune response. Thus, clinical LCH manifestations range from isolated disease with mono- or multifocal bone lesions to disseminated multisystem disease. LCH is a rare disease, affecting mainly children and young smokers, aged 20-50 years. Lung involvement in LCH usually presents as a mono-system disease and is characterized by Langerhans cell granulomas (LCG) infiltrating and impairing the distal bronchioles. The definite diagnosis is based on lung biopsy of CAT selected LCG areas. So far, there is no an effective treatment, but the better understanding of the mechanisms involved in the pathogenesis of the disease would help in the development of effective therapeutic strategies in the future.